PENGUKURAN KINERJA TENAGA KERJA PADA KONTRAKTOR DALAM UPAYA PENINGKATAN KUALITAS BANGUNAN - Irawan, Dafid (WIDYA TEKNIKA, 2010)
The objective of this research is to provide policy recommendations to be implemented by the "Department of Public Works, Construction Services and the Association of Certification Bodies for Construction Services", in the standardization of the quality of workers off on contractors to realize the right job quality, time and cost. Analysis of main factors affecting the quality of freelance workers at the middle contractor, then determine an alternative solution which then determined the most appropriate steps in improving the quality of workers separated. AHP method will be used to perform the selection of alternative solutions to obtain the formulation of recommendations. From the analysis recommended that the three most important items related to improving the quality of freelance workforce is the advancement and technological change (13.2%), the competition for corporate business (9%), the needs and improving the working standards (8.4%). Aspects of the technology is the category that most considered as a factor affecting the increase in labor quality. Internally, the item is considered is the development of interests and talents in relation to the motivation, experience, organization of work in relation to the work environment and workers had attended training in relation to wages. Externally, the most items to be considered is the cost and time for training manpower in relation to the economy and progress, changes in technology in conjunction with technology and business competition in conjunction with business competition.